Marriage Registration as an Instrument of Legal Certainty: A Normative Analysis of the Dualism Between National Law and Islamic Law - Zahra Tania Rafa; Siti Halimah Tusakdiah; Asrizal Saiin (Jurnal Ad Dustur, 2026)
This study originates from the background of the essential role of marriage registration in the Indonesian legal system, as the absence of state registration despite the religious validity of marriage through consent (ijab qabul), witnesses, and dowry creates a legal gap that affects social legitimacy and the protection of family rights. The purpose of this research is to analyze the urgency of marriage registration from the perspectives of Islamic law and national law by examining its normative, juridical, and sociological dimensions. Employing a normative legal research method combined with Gustav Radbruch’s theory of legal certainty and the Islamic principles of maqāṣid al-sharī‘ah, this study explores the function of registration in ensuring legal order and protection. The findings reveal that unregistered marriages generate serious consequences, particularly for women and children, including loss of inheritance rights, lack of legal recognition, and increased vulnerability to injustice. The study concludes that marriage registration represents a form of maslahah mursalah and sadd al-dharā’i‘ that aligns with constitutional guarantees, and it plays a dual role as an instrument of rights protection and social justice as well as a safeguard for the sanctity of marriage within the state’s legal framework.